Axiological dimension of sport as a worldview - Batsunov, Sergey N. (Linguistics and Culture Review, 2021)
The purpose of the study is to analyze the problem of the relationship between culture and sport through the development of a system of values. The research analyses the problems of the unity of sports and culture in modern society; the specifics of their unity and struggle; the influence of sports on the aesthetic abilities of a person, one’s decency, morality, on social relations; comparison of sports with other social values and definitions of cultural values that are developed in the field of sports. The main problem was investigated in the work with methods of analysis and synthesis, which were used to study the origins of classical literature. Its systematization was based on the historical-retrospective principle. The methodology of the analysis includes implicitly the unity of dialectical, systemic, comparative approaches. The research results were accompanied by the achievement of the main requirements of the dialectical methodology, including the principles of transition from the abstract to the concrete, the unity of the historical and the logical, the cognitive-theoretical, and the socio-practical.